Dopamine and 24-Epibrassinolide Upregulate Root Resilience, Mitigating Lead Stress on Leaf Tissue and Stomatal Performance in Tomato Plants - Lohana Ribeiro Prestes; Madson Mateus Santos da Silva; Sharon Graziela Alves da Silva; Maria Andressa Fernandes Gonçalves; Bruno Lemos Batista; Ivan Becari Viana; Allan Klynger da Silva Lobato (Agronomy)
Soil contamination linked to anthropogenic activities has become a serious environmental problem on a global scale. It is caused by heavy metals, such as lead (Pb). Dopamine (DOP) is a biogenic amine that acts as a neurotransmitter. It is found in plant organs and induces tolerance against abiotic stresses, including contamination. 24-epibrassinolide (EBR) stimulates metabolism, positively impacting flowering and production. This research aimed to evaluate whether EBR and DOP, applied alone or combined, can mitigate the impacts caused by Pb on roots and leaves by measuring root and leaf structures and stomatal behavior. For roots, both plant growth regulators maximized the epidermis, with increases in treatments Pb2+ − DOP + EBR (45%), Pb2+ + DOP − EBR (24%), and Pb2+ + DOP + EBR (36%), when compared with equal treatment without Pb2+. To leaves, the tested molecules improved the leaf structures, significantly increasing palisade parenchyma and spongy parenchyma. Parallelly, stomatal performance was boosted after treatments with EBR and DOP, confirmed by increments in stomatal density. Our study proved that EBR and DOP, alone or combined, mitigated the damages to leaves and roots exposed to Pb stress, but better results were found when EBR was applied alone.